2017
DOI: 10.1016/j.eats.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Autologous Minced Cartilage Repair Technique

Abstract: Articular cartilage defects at the knee joint are identified and treated with increasing frequency. Autologous chondrocytes may have the strongest potential to generate high-quality repair tissue within the defective region. Autologous chondrocyte implantation is not available in every country. We present a surgical technique where the surgeon can apply autologous chondrocytes in a one-step procedure to treat articular cartilage defects at the knee joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 22 publications
0
44
0
4
Order By: Relevance
“…The autologous minced (or particulate) cartilage procedure represents a possible alternative. 4,8,44 After initial reports from Albrecht 1 in the early 1980s, Lu et al 24 were the first to pick up the topic of cartilage piece implantation in the 2000s again. Animal models demonstrated that articular chondrocytes that are brought into a defective region are capable of migrating from their surrounding matrix and establishing a new matrix or that transplanted chips can incorporate within the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The autologous minced (or particulate) cartilage procedure represents a possible alternative. 4,8,44 After initial reports from Albrecht 1 in the early 1980s, Lu et al 24 were the first to pick up the topic of cartilage piece implantation in the 2000s again. Animal models demonstrated that articular chondrocytes that are brought into a defective region are capable of migrating from their surrounding matrix and establishing a new matrix or that transplanted chips can incorporate within the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been described before in an open approach. 8 It can be applied arthroscopically at all symptomatic full-thickness cartilage defects of the knee joint including trochlea, both femoral condyles, tibial plateau, and patella surface. In osteochondral defects, a combination of cancellous bone plasty and minced cartilage repair can be performed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Mostly, fragmented cartilage chips are implanted via an open approach. 8 Fixation has been described by the use of fibrin glue, via a membrane, or a combination of both. Autologous chondrocyte implantation (ACI), currently in its fourth generation, can be established via a full arthroscopic approach.…”
mentioning
confidence: 99%
“…They noted a return to the preinjury level of play in both patients, with excellent defect filling on MRI (both patients) and arthroscopy (1 patient). Salzmann et al 10 presented a single-step surgical technique of autologous minced cartilage implantation with fibrin glue. However, an open arthrotomy was used in this technique.…”
Section: Pitfallsmentioning
confidence: 99%